2008
DOI: 10.1051/parasite/2008153206
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondiigene expression is under the control of regulatory pathways acting through chromatin structure

Abstract: Summary :The activity state of a gene is determined by a complex regulatory network of co-acting factors affecting the structure of the chromatin into which the gene is embedded. While significant changes of the transcriptome occur during cell differentiation in apicomplexan parasites, basic mechanisms controlling gene expression are still unknown. Recent studies support and expand the concept of the chromatin environment being key factor for the control of transcriptional activity in these lower eukaryotes or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Collectively, these estimates suggest that the phenotypic differences between type I strains are unlikely to be due to sequence differences (i.e., mutations) but more likely stem from epigenetic differences in gene expression. Recent studies have emphasized the relative importance of epigenetic factors in controlling gene expression in T. gondii (5,16). This suggests that a great deal of phenotypic variation might be expected based on passage history or other environmental influences.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these estimates suggest that the phenotypic differences between type I strains are unlikely to be due to sequence differences (i.e., mutations) but more likely stem from epigenetic differences in gene expression. Recent studies have emphasized the relative importance of epigenetic factors in controlling gene expression in T. gondii (5,16). This suggests that a great deal of phenotypic variation might be expected based on passage history or other environmental influences.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the regulation of gene expression in T. gondii , we and others took advantage of HDAC inhibitors that alter the writing of the histone code and thereby gene transcription (Boyle et al. , 2006; Bougdour et al. , 2008).…”
Section: Interfering With the Epigenome To Understand Gene Expressionmentioning
confidence: 99%
“…, 2008). We showed that specific inhibition of TgHDAC3 by the cyclopeptide FR235222 disrupts the steady‐state level of histone H4 acetylation across the genome inducing derepression of stage‐specific genes (Bougdour et al. , 2008).…”
Section: Interfering With the Epigenome To Understand Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is intriguing in light of the complex life cycle of the parasite, which inevitably requires tight gene regulation. Despite the paucity of recognizable TFs, apicomplexa are endowed with a rich repertoire of enzymes associated with epigenetics and chromatin remodeling, and this observation has fueled the idea that epigenetics could play an important role in the control of gene expression (7,17,34). Therefore, chromatin regulators make suitable targets for the development of therapeutics.…”
mentioning
confidence: 99%